THE EFFECTIVENESS OF MULTICULTURAL BASED INDONESIAN TEACHING MATERIALS TO IMPROVE CRITICAL THINKING SKILLS - Sony Ari Wibowo; Murtono Murtono; Sri Utaminingsih (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
This study aimed to describe the effectiveness of multicultural-based Indonesian teaching materials to improve students’ critical thinking skills at grade IV elementary schools in Kabupaten Jepara. The type of this study was Research and Development (R & D). The teaching materials were tested at grade 1 SD Tritis and SD 1 Karangnongko as the experiment groups and SD 1 Daren and SD 3 Nalumsari as the control groups. Data collection was conducted through observation, interviews, and documentation. Indonesian teaching materials were developed based on the multicultural based Indonesian teaching materials on the theme 4 “various jobs”at grade IV elementary school. Results showed that multicultural based Indonesian teaching materials was effective to enhance the students’ critical thinking skills at grade IV elementary schools in Kabupaten Jepara. The results of t-test on the experimental and control groups was 8.994, which indicated that tcount >ttable (8.994 > 1.699). Hence, Ho was rejected and Ha was accepted. Based on this result, it could be concluded that utilizing multicultural based Indonesian teaching materialswas effective and fit to improve the students’ critical thinking skills at grade IV elementary schools in Kabupaten Jepara.